Parenting Management Of Santri Mutawasithoh Islamic Boarding School Nurul Huda Purbalingga - Mubarok, Ali (Prosiding University Research Colloquium, 2021)
The parenting style applied in the dormitory tends to be authoritarian or centered on one figure only. Through this coaching style, it is hoped that students will obey and develop in the direction expected by the Islamic boarding school. The authoritarian parenting style affects the condition of students living in Islamic boarding schools when compared to other parenting patterns such as permitive and democratic. One of the prominent influences on student discipline. Therefore, caregivers must familiarize students with a series of boarding school activities and obey the applicable regulations. Strategies to achieve the goal of disciplining students, among others, are through the example of their caregivers through advice, guidance and ta'zir (punishment). Therefore, it is very interesting to take a study on the pattern of parenting held at the Islamic Islamic Boarding School Nurul Huda Purbalingga. Because the number of students reaches 1,200 students. This research method uses a qualitative approach, with a field research model. Researchers went directly to the pesantren to dig up data and information through observation and interviews with related parties, such as the head of the foundation, mudir (kiai), and the student body or caregiving department, then the results were analyzed using descriptive analysis. This research was conducted at the Islamic Boarding School Nurul Huda Purbalingga, Mutawashitoh son unit. The results showed that the Islamic Boarding School Nurul Huda Purbalingga, especially the Mutawasithoh unit in its care had been managed well and neatly, from planning, organizing, monitoring and evaluating. The pattern of parenting organization in Mutiq Nurul Huda is that a mudir (kiai) gives parenting tasks to the principal, then the principal divides the tasks to the curriculum section and the santri section to carry out these tasks. Kiai is a figure who is always followed and used as an example by his students. A Kiai must have strong management and leadership knowledge in parenting. So that the character of the students can be formed in accordance with the vision, mission and goals that have been proclaimed. The pattern of santri in nurturing students is to always provide direction before the activity begins, provide training and assignments to students, always direct students to follow and obey all existing regulations, always be a role model for students and create a conducive environment for student learning. In the care of the students of Mutawasithoh Nurul Huda, there are factors that support and hinder. Among the supporting factors are the figure of a kiai, adequate human resources, a dormitory system that makes it easier for students to care for students and a comfortable and clean boarding environment so that students can study well. The inhibiting factor is the problem of funding. Many guardians of students are late in paying tuition fees, so that it affects the smooth accommodation and funding of parenting activities.